A Fully Kinetic Perspective on Weakly Active Comets: Symmetric versus Asymmetric Outgassing - Deca,J; Stephenson,P; Divin,A; Henri,P; Galand,M (Copernicus GmbH, 2022)
For more than two years, ESA’s Rosetta mission measured the complex and ever-evolving plasma environment surrounding comet 67P/Churyumov-Gerasimenko. In this work, we explore the structure and dynamics of the near-comet plasma environment at steady state, comparing directly the results of a spherically symmetric Haser model and an asymmetric outgassing profile based on the measurements from the ROSINA instrument onboard Rosetta during 67P’s weakly outgassing stages. Using a fully kinetic semi-implicit particle-in-cell code, we are able to characterise (1) the various ion and electron populations and their interactions, and (2) the implications to the mass-loading process caused by taking into account asymmetric outgassing. Our model complements observations by providing a full 3D picture that is directly relevant to help interpret the measurements made by the Rosetta Plasma Consortium instruments. In addition, understanding such details better is key to help disentangle the physical drivers active in the plasma environment of comets visited by future exploration missions.